Complete and Early Vitrectomy for Endophthalmitis [Letter] - Agrawal S (Dove Medical Press, 2021)
Surbhi Agrawal Sankara Eye Hospital, Bangalore, IndiaCorrespondence: Surbhi AgrawalSankara Eye Hospital, Varthur Road, Kundalhalli Junction, Bangalore, 560037, IndiaTel +919702023675Email dr.agrawalsurbhi@gmail.com View the original paper by Dr Dib and colleagues